‘Anchored narratives' and the interface of law, psychology and semiotics - Jackson, Bernard S. (Legal and criminological psychology, 1996)
Narrative has become an important paradigm in both psychology and semiotics (Section 1). Three applications of narrative theory to fact finding in criminal cases—Bennett & Feldman (1981), Jackson (1988a, derived from the semiotics of Greimas), Wagenaar (1995; Wagenaar, van Koppen & Crombag, 1993)—are here compared in terms of their conceptions of narrative, application to the courtroom process itself, and epistemological assumptions (Sections 2-4). A recent English case, regarded by some as a miscarriage of justice, is used as a case study to illustrate different approaches from psychology and semiotics (Section 5). The Conclusion (Section 6) considers the potential ‘remediability’ of the courtroom search for truth implied by these various approaches, and the implications of this analysis for the interdisciplinary study of witness testimony and jury research in the ‘normal’ case (where there is no suggestion of miscarriage of justice).